PENGEMBANGAN LEMBAR KERJA SISWA PRAKTIKUM BERBASIS POE (Predict Observe Explain) DENGAN PhET SIMULASI PADA POKOK BAHASAN HUKUM FARADAY - Yusrizal Maulana Yusuf; Karina Hastuti; Popi Purwanti (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2021)
In the 2013 curriculum, teachers required to be creative in teaching. Using many learning media to improve student interest in teaching and learning process. And the one is using printed learning media like student workship. This research aim to give  convenience for teachers to manage teaching and learning process which emphasizes on students activity or group of student. And also helping teachers to directing students to find concepts in theory. This worksheet contain practicum activities which is useful to upgrade students creativities and also can see for real subject matter that discussed. This research using R&D method which is using 4D development style, but only up to develop step. The result of this research from expert validation have average percentage 84 % and from linguist have average percentage 83 %.